ASPECTS OF READING ACQUISITION (Editor: John T. Guthrie) - Aulis, Mark (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1978)
John T. Guthrie, Editor. ASPECTS OF READING ACQUISITION. Baltimore: The John Hopkins University Press, 1976. 222 pp. 3.95 (paper).